The sustainability of public debt in Romania in economic and financial crisis - Dobranschi, Marian (Studies and Scientific Researches. Economics Edition, 2010)
Public finances are key driver in the EU for economic recovery as the debth of the recession and credit constraints require fiscal policy action. This paper emphasis the needed review of public debt and its role in economic development as a particular challenge for emerging economies such as Romania. We explore the most important effects of public debt on economic growth like crowding-out effect, the realtionship between private and public financial transfers, the effect of public debt over GDP growth, inflation and on the sustainability of fiscal policy on the long run. Finnaly we estimate that the composition of public debt can suport debt stabilization and how debt management can stabilize the debt to GDP ratio in face to real returns and outputs growth and thus supports fiscal restraint in ensuring sustainability.